2016
DOI: 10.1002/pro.2990
|View full text |Cite
|
Sign up to set email alerts
|

The urea carboxylase and allophanate hydrolase activities of urea amidolyase are functionally independent

Abstract: Urea amidolyase (UAL) is a multifunctional biotin-dependent enzyme that contributes to both bacterial and fungal pathogenicity by catalyzing the ATP-dependent cleavage of urea into ammonia and CO 2 . UAL is comprised of two enzymatic components: urea carboxylase (UC) and allophanate hydrolase (AH). These enzyme activities are encoded on separate but proximally related genes in prokaryotes while, in most fungi, they are encoded by a single gene that produces a fusion enzyme on a single polypeptide chain. It is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 51 publications
(110 reference statements)
3
22
0
Order By: Relevance
“…If there is no covalent linkage between the AH and UC domains, the latter is not strong enough to hold them to form a stable complex. This suggests that AH and UC encoded by separated genes probably do not form a KlUA-like complex, consistent with studies on a number of such AH and UC proteins [ 16 , 18 , 32 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…If there is no covalent linkage between the AH and UC domains, the latter is not strong enough to hold them to form a stable complex. This suggests that AH and UC encoded by separated genes probably do not form a KlUA-like complex, consistent with studies on a number of such AH and UC proteins [ 16 , 18 , 32 ].…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, substrate channeling of allophanate within the same KlUA polypeptide or KlUA holo-enzyme is unlikely to play a role in the catalysis. A recent study on the Pseudomonas syringae UC and AH also ruled out the possibility that they form a transit complex to facilitate substrate channeling of allophanate during the catalysis [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the significance of this observation is unclear because inhibition was only observed when PxpB was expressed alone and not when PxpB and PxpC were co-expressed to form a complex, as our data show they normally would be. It has also recently been shown that certain fused pxpB and pxpC family genes, which cluster strongly with a urea carboxylase gene, are involved in urea catabolism and encode an enzyme with allophanate hydrolase activity (40,43). Allophanate hydrolase activity has only been demonstrated in a fused PxpBC homolog (43), but it is possible that other PxpB and PxpC proteins have dual roles in OP and urea metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…It has also recently been shown that certain fused pxpB and pxpC family genes, which cluster strongly with a urea carboxylase gene, are involved in urea catabolism and encode an enzyme with allophanate hydrolase activity (40,43). Allophanate hydrolase activity has only been demonstrated in a fused PxpBC homolog (43), but it is possible that other PxpB and PxpC proteins have dual roles in OP and urea metabolism. Additionally, the prokaryote-type OPase genes of Ralstonia solanacearum were shown to be required for pathogenesis in tomato (44).…”
Section: Discussionmentioning
confidence: 99%
“…To ensure vector compatibility, the pET-28a vector encoding ΔBCΔBCCP RePC was modified to replace the pBR322 origin of replication with a pSC101 origin of replication. The gene encoding ΔBCΔBCCP RePC was re-cloned into vector pKLD66nCBP 31 . The T882A mutation was introduced into both ΔBC RePC and ΔBCΔBCCP RePC by whole plasmid mutagenesis using the Quikchange method.…”
Section: Methodsmentioning
confidence: 99%